'Seroprevalence of house dust mites allergen among allergic patients in HUSM' - Ahmad Fathi, Fauzi (Universiti Sains Malaysia, 2006)
This final year research project is about determination of dust mites prevalence among allergic patients in HUSM. There are many type of allergic and my hypothesis is over half of the allergic patients is due to dust mites. From twenty samples that been tested with ELISA method, only one samples showed positive result. And from chi-square test, it has been determined that there is significant association between difference IgE level and the age, sex and race. Several factor regarding validity of the sample, collecting and processing have been written down as reason how such results have been achieved.